2021
DOI: 10.1371/journal.pone.0248391
|View full text |Cite
|
Sign up to set email alerts
|

Planning for work: Exploring the relationship between contraceptive use and women’s sector-specific employment in India

Abstract: While the health-related benefits of contraceptive use for women are well documented, potential social benefits, including enabling women’s employment, have not been well researched. We examine the relationship between contraceptive use and women’s employment in India, a country where both factors have remained relatively static over the past ten years. We use data from India’s 2015–16 National Family Health Survey to test the association between current contraceptive use (none, sterilization, IUD, condom, pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…This may be attributed to several reasons, such as fear of potential side effects hindering their ability to work effectively, cultural beliefs or perceptions favouring permanent and traditional methods, and challenges to accessing and adherence to temporal methods [ 30 ]. This finding coincides with a study conducted in India by McDougal et al which revealed that some women in the working class utilize traditional and permanent methods more than temporary methods [ 31 ]. One sub-Saharan African study offered a plausible explanation by asserting that women generally opt for specific contraception methods based on their reproductive health circumstances and choose traditional methods when they want to use less effective forms of contraception [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…This may be attributed to several reasons, such as fear of potential side effects hindering their ability to work effectively, cultural beliefs or perceptions favouring permanent and traditional methods, and challenges to accessing and adherence to temporal methods [ 30 ]. This finding coincides with a study conducted in India by McDougal et al which revealed that some women in the working class utilize traditional and permanent methods more than temporary methods [ 31 ]. One sub-Saharan African study offered a plausible explanation by asserting that women generally opt for specific contraception methods based on their reproductive health circumstances and choose traditional methods when they want to use less effective forms of contraception [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…might increase the socioeconomic status leading to the decrease of unmet need frequency, while those who have informal occupation would be otherwise. 21 Based on National Demographic and Health Survey, the majority of Papua have informal occupation on agricultural sector. Jakarta ranked as the highest above all provinces in formal occupation employment.…”
Section: Results Demographic Pro Lementioning
confidence: 99%
“…It can happen because, with modern contraception use, they will have control over when to have children. So, pregnancy will not interfere with the careers of married couples (McDougal et al, 2021).…”
Section: Resultsmentioning
confidence: 99%